Cytokine Milieu Tends Toward Inflammation in Type 2 Diabetes - Katherine Esposito; Francesco Nappo; Francesco Giugliano; Carmen Di Palo; Myriam Ciotola; Michelangela Barbieri; Giuseppe Paolisso; Dario Giugliano (2003)
It has been postulated that type 2 diabetes is a manifestation of the inflammatory host response (1). Increased inflammatory activity is believed to play a critical role in development of atherogenesis and to predispose established atherosclerotic plaques to rupture (2). Interleukin (IL)-8 is a potent chemoattractant (chemokine) and induces recruitment of neutrophils and T-cells into the subendothelial space, as well as adhesion of monocytes to endothelium (3). IL-18 is a potent proinflammatory cytokine reported to play a role in plaque destabilization and to predict cardiovascular death in patients with coronary artery disease (4). Adiponectin is an …